2015
DOI: 10.1155/2015/808505
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Gastric Mucosal Morphologic Patterns and Histopathological Severity ofHelicobacter pyloriAssociated Gastritis Using Conventional Narrow Band Imaging Gastroscopy

Abstract: Background and Aim. Identifying specific gastric mucosal morphologic patterns useful for detecting Helicobacter pylori associated gastritis and correlation with histopathological severity. Methods. The endoscopists classified the C-NBI gastroscopic findings into 5 gastric mucosal morphologic patterns as follows: type 1: regular arrangement of collecting venules, type 2: cone-shaped gastric pits, type 3: rod-shaped gastric pits with prominent sulci, type 4: ground glass-like morphology, and type 5: dark brown p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
0
17
0
1
Order By: Relevance
“…Magnifying‐NBI is frequently used in Eastern countries but uncommonly in Western countries. The sensitivity and specificity for diagnosis of H. pylori infection were high according to the original classification using non‐magnifying NBI . The sensitivity of NBI for the diagnosis of intestinal metaplasia was significantly higher than that of WLI, although no significant difference was found between the accuracy of WLI and NBI for the diagnosis of H. pylori infection in a multicenter prospective study for the real‐time diagnosis of both WLI and NBI among five Western countries .…”
Section: Iee For Diagnosis Of Kyoto Classification Of Gastritismentioning
confidence: 92%
See 1 more Smart Citation
“…Magnifying‐NBI is frequently used in Eastern countries but uncommonly in Western countries. The sensitivity and specificity for diagnosis of H. pylori infection were high according to the original classification using non‐magnifying NBI . The sensitivity of NBI for the diagnosis of intestinal metaplasia was significantly higher than that of WLI, although no significant difference was found between the accuracy of WLI and NBI for the diagnosis of H. pylori infection in a multicenter prospective study for the real‐time diagnosis of both WLI and NBI among five Western countries .…”
Section: Iee For Diagnosis Of Kyoto Classification Of Gastritismentioning
confidence: 92%
“…The sensitivity and specificity for diagnosis of H. pylori infection were high according to the original classification using non-magnifying NBI. 43,44 The sensitivity of NBI for the diagnosis of intestinal metaplasia was significantly higher than that of WLI, although no significant difference was found between the accuracy of WLI and NBI for the diagnosis of H. pylori infection in a multicenter prospective study for the real-time diagnosis of both WLI and NBI among five Western countries. 45 Contrarily, yellowish-white nodules visualized with NBI, which had a high specificity for the histological finding of lymphoid follicles in H. pylori-positive stomach, is suggested to be a predictive marker of nodular gastritis.…”
Section: Nbimentioning
confidence: 96%
“…Three of the five gastric mucosal morphologic patterns observed by narrow band imaging (NBI) can predict H. pylori positive status with a high accuracy in the same manner . In another study, NBI was compared to the operative link for gastritis assessment and for gastric intestinal metaplasia assessment (OLGA and OLGIM, respectively) staging systems which can separate low‐ and high‐risk groups for gastric cancer (GC).…”
Section: Invasive Testsmentioning
confidence: 99%
“…However, Ang et al 12 have demonstrated, in a multicentre prospective randomised study involving 579 patients, that NBI detected more focal gastric lesions as compared with high-definition WLE (40.6% vs 29%, p=0.003), as well as a greater proportion of intestinal metaplasia (17.7% vs 7.7%, p<0.001). On a similar note, Tongtawee et al 's38 study of 200 patients demonstrated that NBI also reliably identifies gastric mucosal morphological patterns associated with H. pylori infection, which correlated significantly with severity of pathological inflammation grading. A subsequent randomised study39 on 500 subjects noted site-specific biopsy guided by NBI had higher yield of diagnosing Helicobacter , as compared with standard WLE biopsy.…”
Section: Flexible Spectral Imaging Colour Enhancement (Fice)mentioning
confidence: 88%